Inequality, poverty, education : a political economy of school exclusion - Ashurst, Francesca (Palgrave Macmillan, 2014)
This book develops a political economy and a genealogy of school exclusion in order to reveal exclusion to be a symptom of more fundamental issues relating to poverty and inequality, reflected in the role of the state in managing their consequences, particularly regarding juvenile delinquency. It uses archival and documentary evidence to uncover the roots of exclusionary practices in political and economic struggles going back to the 19th century. These conflicts have had decisive effects on key shifts in social and educational policy from the Poor Law Reforms of 1834 to the emergence of the welfare state and the current neoliberal reconstitution of society according to the model of the market. In arguing that competing views of an equitable and just society underlie exclusion, the analysis opens up a space for envisaging radical new approaches and practices for dealing with children in trouble.